Effects of oxygen on metabolic and secretory activities of βTC3 cells - Papas, K.K.; Long, R.C.; Constantinidis, I.; Sambanis, A. (Biochimica et biophysica acta, 1996)
We have investigated the rates of glucose consumption, lactate production and insulin secretion by mouse insulinoma βTC3 cells exposed to high glucose and oxygen concentrations in the range of 132 mmHg (normoxia) to 0 mmHg (anoxia). The rates of glucose consumption and lactate production, and the yield of lactate on glucose were 6.4 ± 0.2 nmol/h − 10 5 cells, 7.7 ± 0.5 nmol/h − 10 5 cells, and 1.2 ± 0.1 respectively, at oxygen concentrations between 132-25 mmHg. These values increased gradually as the oxygen concentration was reduced below 25 mmHg, reaching a maximum value of 12.8 ± 0.4, 23.8 ± 1.1, 1.9 ± 0.1 respectively, at complete anoxia. Insulin secretion remained constant at 360 ± 24 pmol/h − 10 8 cells at oxygen concentrations between 132-7 mmHg, but was inhibited at lower oxygen concentrations, dropping to 96 ± 24 pmol/h − 10 8 cells at 0 mmHg. The rate of insulin secretion in the presence of high glucose under anoxia was significantly higher than the rate of basal secretion (28.2 ± 3.0 pmol/h − 10 8 cells) at normoxia. The secretory properties of βTC3 cells at low oxygen concentrations may have implications in the development of a diffusion-based bioartificial tissue constructs for the long-term treatment of Insulin Dependent Diabetes Mellitus.